Synthesizing comprehensive models for health behavior studies: connecting dots and revealing links on health enhancement through a meta-analysis approach - Liao, Ying Kai; Liu, Yo-Yu; Wu, Wann-Yih; Chi, Hsin-Kuang; Huang, Kuo-Chung; Vuong, Bich-Hang (Frontiers in Psychology, 2025)
ObjectiveTo systematically synthesize the impact of autonomy and key theoretical models, including Self-Determination Theory (SDT), Technology Acceptance Model (TAM), Value Adoption Model (VAM), Theory of Planned Behavior (TPB), and Health Action Process Approach (HAPA), on health behavior and behavior change determinants, focusing on self-determination and intrinsic motivation as central drivers of independent health decisions.MethodsA meta-analysis was conducted on 135 studies published between 2005 and 2023, with a total sample size of 53,242 participants. We searched the Web of Science and PubMed databases for relevant literature. The theoretical frameworks explored include SDT, TAM, VAM, TPB, and HAPA. Data analysis was performed using Review Manager 5.4.1 software, with effect size calculated as the standardized mean difference with 95% confidence intervals. Heterogeneity was evaluated using I2 statistics.Results(1) SDT significantly impacted motivation, while TAM and VAM influenced perceived value [SMD = 0.96 > 0.8, 95% CI (0.68, 1.24), P < 0.001]. (2) Implementation intentions, action planning, and coping planning were key moderators of health behavior change (I2 = 65.4%). (3) HAPA's structured planning strategies positively impacted long-term health behavior changes.ConclusionAutonomy, self-determination, and intrinsic motivation play a crucial role in health behavior change. Integrating theoretical models such as SDT, TAM, VAM, and HAPA facilitates structured approaches to health interventions, emphasizing implementation intentions, action planning, and coping strategies.